Persepsi pengunjung terhadap minat menginap pada Namira Hotel Syariah Yogyakarta - Yulita, Zarima; Prasetyo, Heri (Journal of Economics, Business, Accounting and Management, 2024)
This research aims to determine visitors' perceptions of price and service quality in Islamic perceptions and their impact on intation in staying at the Namira Hotel Syariah Yogyakarta. This type of research is quantitativxe research with variables X1 Price and X2 service quality. Meanwhile, the dependent variable in this research is Y Interest in staying overnight. The sampling technique in this research was to use a convenience sampling technique. The data collection technique in this research was to use a questionnaire which was distributed widely to respondents of the Namira Hotel Syariah Yogyakarta. The data analysis technique in this research uses descriptive techniques, classical assumptions and multiple linear regression. The results of this research show that visitors' perceptions of price partially have a significant effect on interest in staying at 0.433 with a t-count of 6.767 with a significance of 0.05% and df (N-k-1) or 266-3-1=262, so a t-table of 1.969 is obtained. Visitors' perceptions of service quality partially have a significant effect on interest in staying overnight at 0.355 with a t-count of 6.867 with a significance of 0.05% and df (n-k-1) or 266-3-1=262, so a t-table of 1.969 is obtained. Visitors' perceptions of price and service quality simultaneously influence interest in staying at Namira Syariah Hotel Yogyakarta.